2018
DOI: 10.1021/acs.biochem.8b00559
|View full text |Cite
|
Sign up to set email alerts
|

Allosteric Activation Shifts the Rate-Limiting Step in a Short-Form ATP Phosphoribosyltransferase

Abstract: Short-form ATP phosphoribosyltransferase (ATPPRT) is a hetero-octameric allosteric enzyme comprising four catalytic subunits (HisGS) and four regulatory subunits (HisZ). ATPPRT catalyzes the Mg2+-dependent condensation of ATP and 5-phospho-α-d-ribosyl-1-pyrophosphate (PRPP) to generate N1-(5-phospho-β-d-ribosyl)-ATP (PRATP) and pyrophosphate, the first reaction of histidine biosynthesis. While HisGS is catalytically active on its own, its activity is allosterically enhanced by HisZ in the absence of histidine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
76
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(84 citation statements)
references
References 51 publications
7
76
1
Order By: Relevance
“…Pa ATPPRT catalysis follows an ordered mechanism in which PRPP binds first to the enzyme and involves a burst of on-enzyme PRATP formation in the first turnover followed by a lower steady-state rate dominated by product release. 11 When ATP and histidine are rapidly mixed with Pa ATPPRT preincubated with PRPP (Figure 2A), the amplitude of the burst phase, whose values are 3.49 ± 0.01 and 3.11 ± 0.01 μM in the presence and absence of histidine, respectively, is unchanged within experimental error. The subsequent steady-state rates, whose values are 16.36 ± 0.01 and 7.56 ± 0.01 μM s –1 in the absence and presence of histidine, respectively, reflect the inhibition.…”
Section: Resultsmentioning
confidence: 88%
“…Pa ATPPRT catalysis follows an ordered mechanism in which PRPP binds first to the enzyme and involves a burst of on-enzyme PRATP formation in the first turnover followed by a lower steady-state rate dominated by product release. 11 When ATP and histidine are rapidly mixed with Pa ATPPRT preincubated with PRPP (Figure 2A), the amplitude of the burst phase, whose values are 3.49 ± 0.01 and 3.11 ± 0.01 μM in the presence and absence of histidine, respectively, is unchanged within experimental error. The subsequent steady-state rates, whose values are 16.36 ± 0.01 and 7.56 ± 0.01 μM s –1 in the absence and presence of histidine, respectively, reflect the inhibition.…”
Section: Resultsmentioning
confidence: 88%
“…Supporting a role in catalysis, Asp26 is highly conserved among TrmK orthologues; however, in B. subtilis TrmK, replacement of the equivalent residue Asp29 for alanine had a detrimental but not completely impairing effect on catalysis (9). Moreover, similar reactions where adenine N1 acts as a nucleophile have been proposed to proceed without general base catalysis (28), likely taking advantage of the transient negative charge on N1 due to a natural resonance structure of adenine (29).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we have shown that hinge twisting between domains I and II of the catalytic domain is the key in controlling catalytic activity and regulation. The catalytic domain of short-form ATP-PRT alone was shown to be poorly active (30,31,53). It is likely that HisZ activates and regulates short-form ATP-PRT, in an analogous fashion to the regulatory domain in long-form ATP-PRT, by controlling the hinge motions at the catalytic domain via noncovalent complex formation.…”
Section: Discussionmentioning
confidence: 99%
“…The ATP-PRT-catalyzed reaction between ATP and PRPP uses an ordered sequential mechanism, and therefore reaction occurs when both substrates are present in the active site. In long-form ATP-PRT, it has been shown that ATP binds first, followed by PRPP (28,29), whereas recent studies suggest that substrate binding may occur in the opposite order in short-form ATP-PRTs (30,31). After reaction, pyrophosphate is released, followed by phosphoribosyl-ATP (Fig.…”
Section: Introductionmentioning
confidence: 99%